POLICY FORMULATION FOR ANTICIPATING THE IMPACT OF ACID RAIN ON PADDY PLANTS USING NORMATIVE JURIDICAL ANALYSIS - Ardiansyah Ramadhan; Helni Murtiarsih Jumhur; Fathan Ananta Nur (Universitas Trisakti, 2024)
Law Number 32 of 2009 Article 57, paragraph 4C that one of the preservations of atmosphere functions regulate efforts to protect against acid rain. One of the effects of acid rain is soil damage to plants, such as what happened to paddy plants. In Indonesia, paddy is one of the priority food sources, but every year, it decreases in several regions. Aims: This study aimed at acid rain's anticipated impact on paddy plants in this case study Bandung Regency. Methodology and results: The approach method in this study is a normative juridical approach, using primary data sources obtained through interviews and journal literature. Then, secondary data from legal literature were analyzed descriptively and qualitatively. The study results show that the Bandung Regency Environmental Service has enforced the law. However, violations still occur by industry and society through vehicle emissions, coupled with the increase in population. One of the efforts to formulate policies to anticipate acid rain in paddy plants is to establish sanctions for violators who still pollute the environment, apply catalytic converters to vehicle exhausts that have the potential to remove NOx, carry out measurements at groundwater measurement stations, water quality information systems (manual or real-time). In addition, the irrigation policy for river water flowing on agricultural land with existing laws is being improved. Conclusion, significance, and impact study: Anticipating the impact of acid rain on rice requires various approaches, both technical and non-technical, as well as further analysis from various policy sectors.